Inconclusive evidence for chain-elongated methionine-derived glucosinolates beyond the family Brassicaceae - Agerbirk, Niels; Koch, Marcus (Biochemical systematics and ecology, 2025)
A literature search for reports of glucosinolates (GSLs) from chain-elongated methionine (ceMet) in plants from the order Brassicales, was carried out taking analytical and botanical quality into account. We prepared an updated Brassicales phylogeny as basis for surveying the distribution of ceMet-derived GSLs. The ceMet-derived GSLs are conclusively known from the crown group family Brassicaceae. Outside Brassicaceae only five reports of decent or good quality were found, and two of them could be dismissed as unconvincing after detailed analysis. The remaining three cases were apparently the only good or decent quality evidence of ceMet-derived GSL outside the Brassicacae, involving MS-detection of 3-butenylGSL and either short or long-chain methylsulfinylalkyl GSLs as minor chromatographic peaks. They were scattered in single accessions of single species from three distant families. These isolated reports need independent, critical confirmation at the highest experimental standards before GSLs from ceMet can be accepted outside the Brassicaceae. Multiple screenings for such GSLs in non-Brassicaceae species were negative, suggesting that this group of GSLs is usually absent from all non-Brassicaceae members of the Brassicales. In contrast, GSLs derived directly from Met without chain elongation are rarely searched for but expectable at low levels from low-specificity biosynthesis throughout the order Brassicales. Future papers reporting ceMet-derived GSLs outside Brassicaeae need to supply conclusive evidence of GSL identity and plant species identity. Proof of biosynthesis from Met requires experiments using isotopically labelled Met or equivalent data. Future reviews of GSL diversity should be transparent regarding conflicts between studies, rather than presenting compiled GSL profiles. For surprising single reports, contamination or parallel evolution should be considered.
Gesehen am 23.10.2025